1971
DOI: 10.1109/proc.1971.8232
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic stabilization of the plasma column in flowing molecular lasers

Abstract: A technique of magnetically stabilizing the position of the plasma column and the resulting inversion region in lower pressure flowing molecular lasers is described.A transverse magnetic field, mutually perpendicular to the discharge axial electric field and the gas flow velocity, is employed to maintain the electrical discharge column parallel with the optic axis. The magnetic stabilization of the discharge is analyzed in terms of the Lorantz forces and the resulting ambipolar drifts of the plasma. A comparis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1972
1972
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…In addition, our configuration considers a bounded domain (see figure 1), with distance between the walls in the same order of magnitude as the arc diameter. Again, this is not a new development and similar configurations were studied in the past [6,[13][14][15][16]. In [15], the setup was also bounded with small distance between the walls but the pressure was much lower (few Torrs).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, our configuration considers a bounded domain (see figure 1), with distance between the walls in the same order of magnitude as the arc diameter. Again, this is not a new development and similar configurations were studied in the past [6,[13][14][15][16]. In [15], the setup was also bounded with small distance between the walls but the pressure was much lower (few Torrs).…”
Section: Introductionmentioning
confidence: 99%
“…Again, this is not a new development and similar configurations were studied in the past [6,[13][14][15][16]. In [15], the setup was also bounded with small distance between the walls but the pressure was much lower (few Torrs). In the above mentioned studies, the balance between the magnetic force and gas flow drag was examined and it was concluded that the experimental data is well described by the equality of the Lorentz force and the aerodynamic drag for a rigid cylinder, which can be written for the force per unit length of the arc as [6,16]:…”
Section: Introductionmentioning
confidence: 99%
“…The data folrFigs. 12-14 were obtained with the magnetically stabilized convectively cooled COZ laser configuration described in [44] and [45]. The data were presented here to show the general qualitative parametric behavior of convectively cooled Cot lasers.…”
Section: B Convective-cooled Lasermentioning
confidence: 92%
“…20: The bowing of the discharge downstream by the gas flow is prevented in this configuration by the application of a magnetic field mutually perpendicular to the gas flow and the collinear optical and discharge axis [44], [45]. This laser configuration is called the transverseflow magnetically stabilized coaxialzdischarge laser (OIs, Vu, B z ) .…”
Section: Proceedings Of the Leee June 1973mentioning
confidence: 99%